STATUS, PROBLEMS AND PROSPECTS OF THE PRECINCT THERAPEUTIC SERVICES IN THE SIBERIAN FEDERAL DISTRICT - M. I. Voevoda; V. M. Chernyshev; O. V. Strelchenko; I. F. Mingazov (SINAPS LLC, 2016)
The article describes the problems associated with the organization of medical aid to the population in the outpatient setting, particularly in the work of the district services. The causes that produced them, as well as measures to optimize the structure and operation of outpatient clinics. Special attention is paid to the personnel policy and streamline the work of local doctors, which should attract and retain specialists in this service, increase their efficiency, accessibility and quality of medical care.